MRI Analysis of the Combined Prospectively Collected AOSpine North America and International Data: The Prevalence and Spectrum of Pathologies in a Global Cohort of Patients With Degenerative Cervical Myelopathy. Issue 14 (15th July 2017) - Nouri, Aria; Martin, Allan R.; Tetreault, Lindsay; Nater, Anick; Kato, So; Nakashima, Hiroaki; Nagoshi, Narihito; Reihani-Kermani, Hamed; Fehlings, Michael G.
Abstract : Study Design: An ambispective analysis. Objective: The aim of this study was to report the global prevalence of specific degenerative cervical pathologies in patients with degenerative cervical myelopathy (DCM) through detailed review of magnetic resonance imaging (MRIs). Summary of Background Data: DCM encompasses a spectrum of age-related conditions that result in progressive spinal cord injury. Methods: MRIs of 458 patients (age 56.4 ± 11.8, 285 male, 173 female) were reviewed for specific degenerative features, directionality of cord compression, levels of spinal cord compression, and signal changes on sagittal T2-weighted imaging (T2WI) and sagittal T1-weighted imaging (T1WI). Data were analyzed for differences between sex using Chi-square tests and geographic variations using Kruskal-Wallis tests. Results: Spondylosis was frequently present (89.7%) and was commonly accompanied by enlargement of the ligamentum flavum (LF) (59.9%). Single-level disc pathology, ossification of posterior longitudinal ligament (OPLL), and spondylolisthesis had a prevalence of ∼10% each. OPLL was accompanied by spondylosis in 91.7%. Klippel-Feil syndrome was observed in 2.0%. The Asia-Pacific region had more OPLL (29%, P = 3 × 10 −11 ) and less spondylolisthesis (1.9%, P = 0.002). Females presented more commonly with single-level disc pathology (13.9% vs . 6.7%; P = 0.013), and males with spondylosis (92.3% vs . 85.6%; P = 0.02) and enlargement of LF (61.4% vs . 49.1%; P = 0.01). C5 to C6 was the most frequent maximum compressed site (39.5%) and region for T2WI hyperintensity (38.9%). T2WI hyperintensity more commonly presented in males (82.4% vs . 66.7%; P < 0.001). Conclusion: This is the largest report on the prevalence and spectrum of pathology in patients with DCM. Herein, it has been demonstrated that degenerative features are highly interrelated, that females presented with milder MRI evidence of DCM, and that variations exist in the prevalence of pathologies between geographical regions. Level of Evidence. 2